2013
DOI: 10.1177/0022466912474102
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Ratio Strategies Intervention on Knowledge of Ratio Equivalence for Students With Learning Disability

Abstract: Students with mathematics learning disabilities have a weak understanding of mathematical concepts that underlie success in Algebra I, such as ratios and proportional reasoning. In this study, researchers used a multiple baseline across participants design to evaluate the effects of a intervention based on a instructional trajectory of how students come to understand ratios through build-up, emergent unit, and unit strategies on performance on a test of ratio equivalence. Student performance during interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 12 publications
1
48
0
12
Order By: Relevance
“…They reported that all three students developed more sophisticated strategies around ratio during the intervention, although the initial baseline of one student was unstable which impacted analysis of that student's growth. They noted that the "results from this study suggest the potential power of instruction that begins with a respect of how students approach solving mathematics problems and then adds meaningful teacher supports and prompts" [54] (p. 189). Indeed, Hunt and Vasquez's work involved a characteristically constructivist approach: the focus was on close attention to student's mathematical thinking, with an assumption that instruction should build on student prior conceptions.…”
Section: Constructivist Theoretical Orientationmentioning
confidence: 89%
See 1 more Smart Citation
“…They reported that all three students developed more sophisticated strategies around ratio during the intervention, although the initial baseline of one student was unstable which impacted analysis of that student's growth. They noted that the "results from this study suggest the potential power of instruction that begins with a respect of how students approach solving mathematics problems and then adds meaningful teacher supports and prompts" [54] (p. 189). Indeed, Hunt and Vasquez's work involved a characteristically constructivist approach: the focus was on close attention to student's mathematical thinking, with an assumption that instruction should build on student prior conceptions.…”
Section: Constructivist Theoretical Orientationmentioning
confidence: 89%
“…Hunt and Vasquez [54] conducted research with three students with learning disabilities, developing an intervention to increase students' understanding of ratio. The intervention consisted of individualized tutoring, based on an instructional trajectory developed from research on the development of multiplicative thinking in the area of ratio [55].…”
Section: Constructivist Theoretical Orientationmentioning
confidence: 99%
“…Soylu (2006, s. 135) da sıfır rakamının öğrenilmesinin diğer rakamlardan daha zor ve soyut olduğunu ifade etmiştir. Zihinsel yetersizliği bulunan öğrencilerin soyut kavramları anlamlandırmakta güçlük yaşadığı (Hunt ve Vasquez, 2014) göz önüne alındığında, öğrencinin bu süreçte sıfır rakamını anlamlandırmasının önemli olduğu söylenebilir. Bu becerilerin yanı sıra çalışmada zihinsel yetersizliği olan öğrencilere öğretim ortamında hoşuna giden nesnelere dayalı sorular sorulduğunda öğrencilerin daha hızlı cevaplar verdiği belirlenmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Bu bağlamda etkileşime dayalı öğrenme ile ilgili elde edilen bulgu alan yazınla örtüşmektedir. Yapılan araştırmalar zihinsel yetersizliği olan öğrencilerin öğrenme sürecinde genelleme yapmada güçlük yaşadıklarını ortaya koymuştur (Camadan vd., 2011;Howard vd., 2011, s. 478;Hunt ve Vasquez, 2014;Pierangelo ve Giuliani, 2004, s. 177). Nitekim bu çalışmada erkek öğrenci soru içeriğinde daha çok ayrıntılara takılıp kaldığından doğru genellemelere ulaşamamıştır.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation